Adsorption and toxicity of heavy metals on activated sludge - Soon-An, Ong; Toorisaka, Eiichi; Hirata, Makoto; Hano, Tadashi (Science Society of Thailand, 2011)
Link to publisher's homepage http://www.scisoc.or.th/